ANALISIS TEGANGAN DI POROS ENGKOL YAMAHA RX KING TAHUN 2005 MENGGUNAKAN PERANGKAT LUNAK SOLIDWORK - Emanuel G. N Dhey; Ishak S. Limbong; Matheus M. Dwinanto (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
The crankshaft is one of the main components that converts the potential energy of the fuel into rotating power for the piston engine. Because in the process of working the crankshaft changes the piston's back and forth motion into a rotating motion of the shaft. To minimize the effects of damage that occurs due to various types of dynamic loads acting on the crankshaft components, the design process should first know the working stress distribution. Meanwhile, as a tool in analyzing it, Solidworks software is used. From the results of this analysis, the location or position of the damage due to too high a loading can be identified early. This the authors in this study want to raise a title, namely "Analysis of Stress in the Crankshaft Yamaha Rx-King Year 2005 Using Solidwork Software". Based on the results of the theoretical calculation with the radial force loading of 1.4 N, the bending moment is 10388.1 N / mm, the normal stress is 33.76 N / mm2 , the shear stress is 10.328 N / mm2, the maximum stress is 33.21 N / mm2, and the minimum stress is 3.55N / mm2. Based on the simulation results with solidwork software, the maximum stress is 4,83511e-007 N / m2. FOS (factor of safety) based on analysis using software obtained by 4.339e + 004 N / m2.